Nursing Work Ergonomics Knowledge Relating to Musculoskeletal Complaints in Inpatient Room RSD Mangusada - I Gede Agus Artana; Putu Wira Kusuma Putra; Desak Putu Risna Dewi (Poltekkes Kemenkes Jakarta III, 2021)
Musculoskeletal disorders (MSDs) are disorders of the musculoskeletal system. Musculoskeletal disorder complaints are caused by incorrect ergonomics. Knowledge or cognitive about ergonomics is a very important domain for the formation of a person's behavior or actions. This study aimed to determine the correlation between associate nurses’ knowledge about working ergonomics with musculoskeletal disorders in inpatient ward of Mangusada Regional Hospital, Badung Regency. This study used an observational analytical research design with cross sectional approach. The number of samples was 51 respondents with purposive sampling technique. Data was collected using knowledge questionnaire about working ergonomics and the Nordic Body Map sheet. Data was analyzed using the Spearman’s rho test. It showed adequate result of associate nurses' knowledge about the working ergonomics were mostly 30 respondents (58.8%) and moderate musculoskeletal disorders of nurses in inpatient ward was (58.8%). The analysis of the correlation between associate nurses’ knowledge about working ergonomics with musculoskeletal disorders obtained p-value <0,000. It can be concluded that there was a correlation between associate nurses’ knowledge about working ergonomics with musculoskeletal disorders in inpatient ward of Mangusada Regional Hospital, Badung Regency. The recommendation of this study is expected to be an input for nurses in working using ergonomics guidelines.